Efficacy of the Brain Injury Family Intervention: Impact on Family Members. Issue 4 (July 2015) - Kreutzer, Jeffrey S.; Marwitz, Jennifer H.; Sima, Adam P.; Godwin, Emilie E.
Abstract : Objective: Examine the effectiveness of an intervention (Brain Injury Family Intervention) for family caregivers after acquired brain injury. Research Design: Prospective, controlled repeated-measures design. Methods: The Brain Injury Family Intervention was designed as a whole family approach to addressing needs, emphasizing education, skill building, and psychological support. One hundred eight families of outpatients were assigned to either a treatment or wait list control group. The manualized treatment focused on highly relevant topics (eg, common injury effects, coping with loss and change, communication, and stress management) and was composed of five 2-hour sessions with outcome measurement pretreatment, posttreatment, and at 3 months following. Outcome measures included the Family Needs Questionnaire, the Service Obstacles Scale, and the Zarit Burden Interview. Results: Treatment group caregivers showed an increase in met needs, greater satisfaction with services, and reduced burden relative to pretesting, whereas controls did not. Between-group differences for Professional Support needs were identified. Conclusions: Investigation provided evidence that a curriculum-based education, skill-building, and support intervention can benefit caregivers for up to 3 months. Additional research is needed to ascertain the longer-term benefits of intervention and the efficacy of alternative delivery methods (eg, via telephone and the Internet). Abstract : Supplemental Digital Content is Available in the Text.